2012
DOI: 10.2527/jas.2011-4311
|View full text |Cite
|
Sign up to set email alerts
|

Application of computer-assisted semen analysis to explain variations in pig fertility1

Abstract: Sperm quality is often evaluated through computer-assisted semen analysis (CASA) and is an indicator of boar fertility. The aim of this research was to study the relationship between CASA motility parameters and fertility results in pigs. Insemination records and semen parameters from a total of 45,532 ejaculates collected over a 3-yr period were used. The statistical model for analysis of fertility data from these inseminations included factors related to sow productivity. The boar- and semen-related variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
153
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(173 citation statements)
references
References 34 publications
11
153
2
7
Order By: Relevance
“…Neither Alh, concentration nor the total number of sperms in the AI dose significantly affected litter size at birth. Our results are in agreement with those of Broekhuijse et al (2011) in pigs, revealing the significant influence of average path velocity on the number of piglets born, but in disagreement concerning the influence of amplitude of lateral head displacement, found to be significant in pigs. The number of total sperms per dose did not significantly influence prolificacy, unlike Tussel et al (2011) who reported a significant increase in prolificacy by increasing the number of sperms/dose from 5 or 20 × 10 6 .…”
Section: Means and Variations Of Reproductive Performancessupporting
confidence: 81%
See 1 more Smart Citation
“…Neither Alh, concentration nor the total number of sperms in the AI dose significantly affected litter size at birth. Our results are in agreement with those of Broekhuijse et al (2011) in pigs, revealing the significant influence of average path velocity on the number of piglets born, but in disagreement concerning the influence of amplitude of lateral head displacement, found to be significant in pigs. The number of total sperms per dose did not significantly influence prolificacy, unlike Tussel et al (2011) who reported a significant increase in prolificacy by increasing the number of sperms/dose from 5 or 20 × 10 6 .…”
Section: Means and Variations Of Reproductive Performancessupporting
confidence: 81%
“…Among these semen parameters, only Lavara et al (2005) obtained a negative but significant correlation between the linearity of sperm movement and fertility (r = −0.32), using heterospermic pools. In pigs, Broekhuijse et al (2011) obtained significant (P < 0.05) effects of progressive motility, curvilinear velocity and beat cross frequency on the farrowing rate. Although the presence of gel plugs in the semen is a major criterion for ejaculate rejection in some AI centres (Piles et al, 2013), our results revealed that this characteristic has no effect on either fertility or prolificacy.…”
Section: Means and Variations Of Reproductive Performancesmentioning
confidence: 90%
“…Until recently, the assessment of sperm motility was based solely on subjective microscopic evaluation of the total proportion of motile spermatozoa with results varying between 30% and 80% (Barros et al, 1973;Budworth et al, 1988;Amann, 1989;Chan et al, 1989;Auger et al, 1993;Broekhuijse et al, 2012). Due to the large variations observed, comparability of the results obtained by different laboratories is questionable (Dott and Foster, 1979).…”
mentioning
confidence: 99%
“…On the other hand, two more recent studies by Broekhuijse et al (2011;2012) showed that progressive motility, VCL and BCF were positively related with farrowing rate, while total motility, VAP, VSL and ALH were positively related to the total number of born piglets. Holt et al (1997) also reported that the VSL was positively related to the litter size.…”
Section: Boar Semenmentioning
confidence: 83%